Multifunctional Adaptive NS1 Mutations Are Selected Upon Influenza A Virus Evolution in the Mouse - Forbes, Nicole E (Université d'Ottawa / University of Ottawa, 2012)
Influenza A virus (IAV) can evolve from low virulence in animal hosts to become highly virulent in humans. Pandemic Influenza A viruses such as the 1918 Spanish Influenza caused over 50 million deaths worldwide. However the genetic determinants of IAV host adaptation and virulence are largely uncharacterized. The IAV NS1 protein is a multifunctional interferon antagonist and a known virulence factor. We hypothesized that NS1 mutations selected upon IAV evolution to a novel host contribute to host adaptation by mechanisms involving increased gene expression and IFN antagonism. To this end, I phenotypically characterized the NS1 mutations selected upon adaptation of A/Hong Kong/1/1968 (H3N2) (HK-wt) to increased virulence in the mouse. Sequencing the NS genome segment of mouse-adapted variants revealed eleven mutations in the NS1 gene and four in the overlapping NEP gene. Using the HK-wt virus and reverse genetics to express recombinant HK NS1 mutant viruses, I demonstrated that all NS1 mutations were adaptive and enhanced virus replication (up to 100 fold) in mouse cells and/or lungs. All but one NS1 mutant was associated with increased virulence measured by survival and weight loss in the mouse. Ten of twelve NS1 mutants significantly enhanced IFN-β antagonism to reduce the level of IFN-β production relative to HK-wt in infected mouse lungs at 1 day post infection, where nine mutants induced viral yields in the lung that were ≥ HK-wt (up to 16 fold increase). Eight of 12 NS1 mutants had decreased binding affinity to the cleavage and polyadenylation specificity factor (CPSF30). The majority of mutant NS1 genes demonstrated increased viral polymerase activity and viral protein production in mouse cells. Viral protein production and viral growth were also assessed in human and canine cell lines; however these adaptive phenotypes were more robust in infected mouse cells. Adaptive NS1 mutations also increased cytoplasmic cellular localization of the NS1 protein in infected cells in a host cell-specific manner. Evaluation of phenotypic trends associated with the NS1 mutants demonstrated an inverse correlation between CPSF30 binding affinity and viral polymerase activity enhancement. This study demonstrates that NS1 is a multifunctional virulence factor subject to adaptive evolution.
Keywords: Influenza; Evolution; Virulence; NS1; Interferon; Adaptation; virus gene expression; viral genetics